Geguritan Begawan Dharma Swami (Kajian Nilai Pendidikan Agama Hindu) - Pradnyana, Gde Bagus Made Surya; Sugita, I Wayan; Mastini, Gusti Nyoman (Jayapangus Press, 2019)
Geguritan is an ancient literary work which has an anonymous or classical literary characteristic which is anonymous, without the name of the author and writer. Geguritan was created to convey a message or safe about the values of life, religion, customs, and a legend. The mandate contained in the poem should be developed and disseminated to the community to enhance knowledge and also the devotion to the creator. Geguritan Begawan Dharma Swami is one of the geguritan which contains very high values of hindu religious education. A Phenomenon that has happened lately, where people are more inclined to lust or kama. We can see this in the example of behavior in society today, many still deviate from religious teachings. Therefore, it can be used as a guideline for the community on how to behave well in line with religious teachings and the researcher make the Geguritan of Dharma swami as an object of research. As for the issues to be discussed, among others : (1) How is the narrative structure of Geguritan Begawan Dharma Swami, (2) The values of any hindu religious education contained in Geguritan Begawan Dharma Swami. This study aims to, (1) Know the narrative structure of Geguritan Begawan Dharma Swami as a traditional literary work. (2) Uncovering the values of hindu religious education contained in Geguritan Begawan Dharma Swami. The Theories used to analyze problem formulation are : structural theori, and value theori. The method used two methods are library and interview method. The data that has been collected is analyzed by qualitative descriptive method with steps of data reduction, data presentation, and conclusion drawing or verification. Based on the analysis carried out, the result of the research are : (1) The narrative structure of Geguritan Begawan Dharma Swami consists of : theme, characterization, incident, plot, setting, and mandate. (2) The values of hindu religious education contained in the Geguritan Begawan Dharma Swami namely : Tattwa values, Tri Hita Karana values, ethical values (Susila), and loyalty values.